81.6k views
4 votes
Directions in pic. Number 15 and also when you graph it do the main function in red and inverse in blue

Directions in pic. Number 15 and also when you graph it do the main function in red-example-1

1 Answer

4 votes

To find the inverse of a function, you have to start by replacing the f(x) by y:


\begin{gathered} f(x)=-x^2+6 \\ y=-x^2+6 \end{gathered}

Now switch the x and y:


x=-y^2+6

Solve for y:


\begin{gathered} \text{Subtract 6 from both sides} \\ x-6=-y^2+6-6 \\ x-6=-y^2 \\ \text{ Multiply both sides by -1} \\ -1(x-6)=-1(-y^2) \\ 6-x=y^2 \\ \text{Apply square root to both sides} \\ \sqrt[]{6-x}=\sqrt[]{y^2} \\ \sqrt[]{6-x}=y \\ \text{Then,} \\ y=\sqrt[]{6-x} \end{gathered}

Finally, replace y by f^-1(x):


f^(-1)(x)=\sqrt[]{6-x}

The graph of the main function is in red, and the graph of the inverse function is in blue:

As you can see, the graph of the inverse function (blue) is the graph of the main function (red) reflected about the diagonal line y=x (orange). Then, the inverse relationship is verified.

Directions in pic. Number 15 and also when you graph it do the main function in red-example-1
User Ayende Rahien
by
6.0k points